2015
DOI: 10.1124/dmd.115.066712
|View full text |Cite
|
Sign up to set email alerts
|

Organic Anion Transporting Polypeptide (OATP)2B1 Contributes to Gastrointestinal Toxicity of Anticancer Drug SN-38, Active Metabolite of Irinotecan Hydrochloride

Abstract: Gastrointestinal toxicity, such as late-onset diarrhea, is a significant concern in irinotecan hydrochloride (CPT-11)-containing regimens. Prophylaxis of late-onset diarrhea has been reported with use of Japanese traditional (Kampo) medicine containing baicalin and with the antibiotic cefixime, and this has been explained in terms of inhibition of bacterial deconjugation of SN-38-glucuronide since unconjugated SN-38 (active metabolite of CPT-11) is responsible for the gastrointestinal toxicity. It is also prer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 38 publications
(57 reference statements)
1
36
0
2
Order By: Relevance
“…Uptake transporters may also have an effect on the disposition of SN-38. SN-38 is known to be transported by human OATP1B1, OATP1B3, and OATP2B1 (Kalliokoski and Niemi, 2009;Fujita et al, 2016), and rodent transporters OATP1B2, OATP2B1, and OATP1A4 (Wang et al, 2016), although other transporters of organic anions may also be involved. The MCD diet has been shown to alter the mRNA and protein expression of various hepatic uptake transporters, including rat OATP1A1, OATP1A3, OATP1B2, and OATP2B1.…”
Section: Discussionmentioning
confidence: 99%
“…Uptake transporters may also have an effect on the disposition of SN-38. SN-38 is known to be transported by human OATP1B1, OATP1B3, and OATP2B1 (Kalliokoski and Niemi, 2009;Fujita et al, 2016), and rodent transporters OATP1B2, OATP2B1, and OATP1A4 (Wang et al, 2016), although other transporters of organic anions may also be involved. The MCD diet has been shown to alter the mRNA and protein expression of various hepatic uptake transporters, including rat OATP1A1, OATP1A3, OATP1B2, and OATP2B1.…”
Section: Discussionmentioning
confidence: 99%
“…OATP1B1 does not transport SN-38 glucuronide (Nozawa et al, 2005a). OATP2B1 transports SN-38 in Xenopus oocytes (Fujita et al, 2016), but not in HEK293 cells (Fujita et al, 2014). Oatp1a/1b null mice have markedly increased plasma exposure of irinotecan and SN-38 and significantly decreased liverto-plasma ratios of these compounds compared with wild type.…”
Section: The Role Of Oatp Transporters In Chemotherapy Dispositionmentioning
confidence: 98%
“…It is spontaneously converted to an active metabolite, 7-ethyl-10-hydroxycamptothecin (SN-38), by hepatic carboxylesterase and butyrylcholinesterase (de Man et al, 2018). SN-38 is believed to play a role in both the efficacy and toxicity associated with irinotecan-containing regimens, especially diarrhea (Kehrer et al, 2001;Fujita et al, 2016). SN-38 is further metabolized to an inactive form, SN-38glucuronide, by uridine diphosphate glucuronosyltransferases, most prominently by the 1A1 isoform (UGT1A1); this glucuronide form is transported to the intestinal lumen via bile (Lokiec et al, 1995;de Man et al, 2018).…”
Section: The Role Of Oatp Transporters In Chemotherapy Dispositionmentioning
confidence: 99%
See 1 more Smart Citation
“…SN-38 and topotecan are pharmacologically active in the lactone form, but most drugs are in the inactive carboxylate form at physiologic pH (Oguma, 2001). With reference to the transport of lactone and carboxylate forms of SN-38, we have recently shown that they are similarly transported by another type of transporter, organic anion-transporting polypeptide 2B1 (Fujita et al, 2016). However, the same result may not be directly applicable to BCRP-mediated transport, and evaluation of the efflux ratio of the lactone forms of these drugs separately from their carboxylate forms will be required.…”
Section: Panc-1mentioning
confidence: 99%